Foundations of a Marxist Theory of the Political Economy of Information: Trade Secrets and Intellectual Property, and the Production of Relative Surplus Value and the Extraction of Rent-Tribute - Jakob Rigi (tripleC: Communication, Capitalism & Critique)
The aim of this article is to sketch a preliminary outline of a Marxist theory of the political economy of information. It defines information as a symbolic form that can be digitally copied. This definition is purely formal and disregards epistemological, ideological, and functional aspects. The article argues that the value of information defined in this sense tends to zero and therefore the price of information is rent. However, information plays a central role in the production of relative surplus value on the one hand, and the distribution of the total social surplus value in forms of surplus profits and rents, on the other. Thus, the hegemony of information technologies in contemporary productive forces has not made Marx’s theory of value irrelevant. On the contrary, the political economy of information can only be understood in the light of this theory. The article demonstrates that the capitalist production and distribution of surplus value at the global level forms the foundation of the political economy of information.